Hubungan Kepercayaan Diri dengan Kecerdasan Kinestetik Anak Usia 5-6 Tahun di TK IT Al-Ittihad Rumbai Pesisir Kota Pekanbaru - Mastura; Ria Novianti; Enda Puspitasari (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2020)
This research is based on observations of researchers at TK IT Al-Ittihad Rumbai PesisirPekanbaru City. In this observation the researchers concluded that kinesthetic intelligence requires good self-confidence. The purpose of this study was to determine the relationship of Confidence with Kinesthetic Intelligence in Children Aged 5-6 Years at TK IT Al-Ittihad Rumbai Pesisir, Pekanbaru City. This research is a quantitative study with the type of correlation research. The study population was children aged 5-6 years in TK IT Al-Ittihad Rumbai Pesisir Pekanbaru City, with the sample used amounted to 30 children aged 5-6 years. The data collection technique used is observation. Analysis of the study used Pearson product moment correlation test with nominal data characteristics with the help of SPSS IMB ver.24. Based on the calculation results of the correlation test, the results of the bivariate correlation coefficient obtained between Confidence with kinesthetic intelligence of rxy = 0.964. This shows that there is a relationship between self-confidence with kinesthetic intelligence. As an evaluation criterion, if probability> 0.05 then Ho is accepted, whereas if probability <0.05 then Ho is rejected (Syofian, 2014). In the correlation test table results obtained a probability number of 0,000, where 0,000 <0.05 then Ho is rejected. This means that there is a significant positive relationship between the two variables.